THE INFLUENCE OF CREATOR CONTENT ON BRAND IMAGE ON TIKTOK SAMPO KEMAIU - Safitri, Dian Ayu; Mandasari, Virginia (Yayasan Education and Social Center, 2024)
This research aims to understand the impact of creator content on brand image on the TikTok social media platform, especially in the context of the product